The Effect of Foreign Buy and the Dow Jones Index on Stocks Prices of Animal Feed Industry at Kompas 100 - Ryan Elfahmi (Kusuma Negara Business School, 2020)
This research aims to determine whether foreign buy and the Dow Jones index have an effect on stock prices. This study uses a quantitative approach. The research scope is the stocks of companies in the animal feed industry which are listed on the Kompas 100 Index on the Indonesia Stock Exchange. Data in the form of secondary data obtained from the Indonesia Stock Exchange through www.idx.co.id. Eviews 9 software is used to select the research model, classic assumption test, multiple correlation test, multiple linear regression analysis, hypothesis t test and determination coefficient test. Based on the results of this study, it was found that foreign buy had an effect on stock prices, while the Dow Jones Index had no effect on stock prices.